Application of Social Cognitive Theory as a Predictor for Health Screening Utilization among Pre-Marital Couples - Fifi Fidyaningrum; Argyo Demartoto; Bhisma Murti; Happy Indri Hapsari; Revi Gama Hatta Novika (Masters Program in Public Health, Sebelas Maret University, 2025)
Background: Circumstances in the early stages of development have a tremendous impact on a person's risk of developing diseases in adulthood. Numerous diseases can start in childhood and are generated by various traumas in early life, including improper treatment during pregnancy, maternal malnutrition, and maternal disease, one of which is diseases related to reproductive health. Premarital health screening is a series of tests that must be carried out by prospective brides and grooms before marriage, which aims to reduce the burden of inherited diseases by reducing the number of high-risk marriages. This study aimed to analyze the use of health screening among pre-marital couples through the Social Cognitive Theory. Subjects and Method: A cross-sectional study was conducted in Nias, Indonesia, in October-November 2024. A sample of 200 brides and grooms was selected using fixed disease sampling. The data were collected using questionnaire and analyzed using a path analysis. Results: Outcome expectation was positively and indirectly associated with pre-marital health screening (b= 0.58; 95% CI= 0.01 to 1.15; p= 0.046). Knowledge, reinforcement, and observational learning were indirectly associated with pre-marital health screening among pre-marital couples. Conclusion: Social cognitive theory can be used to predict health screening uptake among pre-marital couples.